1997
DOI: 10.1152/jappl.1997.82.5.1479
|View full text |Cite
|
Sign up to set email alerts
|

Methacholine-induced bronchoconstriction in rats: effects of intravenous vs. aerosol delivery

Abstract: To determine the predominant site of action of methacholine (MCh) on lung mechanics, two groups of open-chest Sprague-Dawley rats were studied. Five rats were measured during intravenous infusion of MCh (i.v. group), with doubling of concentrations from 1 to 16 micrograms.kg-1.min-1. Seven rats were measured after aerosol administration of MCh with doses doubled from 1 to 16 mg/ml (ae group). Pulmonary input impedance (ZL) between 0.5 and 21 Hz was determined by using a wave-tube technique. A model containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
168
3
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 29 publications
11
168
3
8
Order By: Relevance
“…The average contribution of the chest wall to R was 6%, and the average contribution to G was 20%. These contributions are of similar proportions to studies that used similar techniques in other species, including rats (14) and human infants (Z. Hantos and P. Sly, unpublished observations). Perhaps surprisingly, our results suggest that the elastic properties of the chest wall do not contribute to the elastic behavior of the respiratory system.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The average contribution of the chest wall to R was 6%, and the average contribution to G was 20%. These contributions are of similar proportions to studies that used similar techniques in other species, including rats (14) and human infants (Z. Hantos and P. Sly, unpublished observations). Perhaps surprisingly, our results suggest that the elastic properties of the chest wall do not contribute to the elastic behavior of the respiratory system.…”
Section: Discussionsupporting
confidence: 60%
“…Ventilation inhomogeneity with partial closure of some peripheral airways would be expected to result in an increase in G that is not matched by a similar increase in H and an increase in . Studies in rats undergoing methacholine challenge showed such a pattern (14) and confirmed that peripheral inhomogeneity was indeed responsible by ventilating the animals with a gas mixture of 20% oxygen and 80% neon and showing gas-dependent changes in G. We approached this possibility in several ways. We first considered that the volume history set by a PEEP of 2 cmH 2 O might not have been sufficient to prevent atelectasis and/or ventilation inhomogeneity from developing in our anesthetized, supine animals.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Suki et al (27) have reported that, in open-chest dogs, the pulmonary constrictor responses elicited by methacholine were diminished relative to those obtained in the same animals in closed-chest conditions. Petá k et al (22) have shown that the aerosol administration of methacholine produced greater elevations of Hti and Gti than those caused by the intravenous administration of methacholine. On histology, methacholine delivered as an aerosol has been shown to produce more heterogeneous reductions in airway diameters and greater distortion of the lung parenchyma compared with those associated with the intravenous administration of methacholine.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Z rs was measured using a wave‐tube system 42 adapted for use in small animals 41 , 43 . Oscillatory signals consisting of nine non‐integer multiple frequency components between 4 and 38 Hz were delivered via a 1 m wave tube (internal diameter = 0·116 cm) to tracheostomized mice during brief apnoeic periods.…”
Section: Methodsmentioning
confidence: 99%